Trustworthy Retrieval-Augmented Generation for Adversarially Robust Medical Large Language Model Agents - Shane Bush; Leonard Bamos (International Journal of Clinical and Translational Medicine, 2026)
The rapid integration of large language models into clinical decision support has created a new class of medical artificial intelligence agents capable of synthesizing vast medical knowledge, yet their safe deployment is undermined by adversarial threats and unresolved trustworthiness gaps. This paper examines the design space for retrieval-augmented generation architectures that serve as the cognitive core of these agents, focusing on the interplay between adversarial robustness, clinical reliability, and system-level governance. We argue that simply inserting a retrieval component into a generative model does not inherently confer trustworthiness; rather, it introduces a complex sociotechnical surface that adversaries can exploit through data poisoning, prompt injection, and corpus manipulation. Starting from a system-of-systems perspective, we dissect the layered infrastructure of medical large language model agents, analyze the emergent adversarial attack taxonomy specific to retrieval-augmented generation, and articulate architectural principles for embedding robustness without sacrificing clinical performance. The discussion extends to structural trade-offs involving latency, fairness, sustainability, and regulatory alignment, emphasizing that trustworthiness cannot be localized to a single model module but must be distributed across data governance, retrieval curation, model alignment, and human oversight. Policy implications for medical device regulation, continuous monitoring, and multi-stakeholder accountability are explored. By synthesizing cross-domain insights from machine learning security, health informatics, and infrastructure studies, we outline a holistic framework for building adversarially resilient medical agents that retain the flexibility of retrieval-augmented generation while upholding rigorous safety standards.